Impact of real-time PCR on Whipple’s disease diagnosis: the experience of Fondazione IRCCS Policlinico San Matteo - I. Mileto; C. Merla; D. De Vitis; M. Ardizzone; M. Corbella; F. Biagi; P. Cambieri (Microbiologia Medica)
Not available.